Perkembangan Pendidikan di Cina dan India - Kusmawati, Heny; Mubarokah, Siti Lailatul; Abidin, Mochamad Zaenal (PT Literasi Nusantara Publisher, 2023)
Education is very influential for life. Education can develop an advanced society and nation. Each country has characteristics in its education system. As in China and India, the formation of the education system was influenced by figures who brought major changes to their countries. Starting from the education system in China, which was influenced by the Kung Fu Tze system which is a philosopher who brought change, not only in education but in the political, social and cultural world. The beginning of ancient Chinese education reached its peak starting in the Han Dynasty, where the teachings of Tse Kung Fu were again raised and applied in the life of Chinese society. Meanwhile, the education system in India during the classical system was dominated by the caste system. In its implementation, it is the Brahmin caste that plays a role. But around the 20th century, Rabindranath Tagore was a pioneer of enlightenment in Santiniketan. In the field of education, Tagore has brought in a class base in nature.